Nanocomposites CoPt-x/Diatomite-C as oxygen reversible electrocatalysts for zinc-air batteries: Diatomite boosted the catalytic activity and durability - Wang, Kai; Tang, Zhenghua; Wu, Wen; Xi, Pinxian; Liu, Dong; Ding, Zhaoqing; Chen, Xiaoning; Wu, Xiao; Chen, Shaowei (Electrochimica acta, 2018)
The exploration of oxygen reversible electrocatalysts to boost oxygen reduction reaction and oxygen evolution reaction is critical for the development of high-performance aqueous Zn-air batteries. Since diatomite with porous structure can adsorb metal ions in aqueous solution, herein, we prepare the nanocomposite CoPt-x/Diatomite-C for both oxygen reduction and evolution reactions, and diatomite is found significantly promotes the electrocatalytic activity and durability. With the presence of diatomite, CoPt-1/Diatomite-C shows a lower Tafel slope (63 mV dec−1 at high potential range), larger diffusion-limited current density (4.94 mA cm−2) and superior durability for ORR. Particularly, the specific and mass activities of CoPt-1/Diatomite-C for ORR are 0.74 mA cm−2 and 286 mA mg−1, respectively, which are 2.5 and 3.0 times higher than that of CoPt-1/C without diatomite; For OER, the overpotential of CoPt-9/Diatomite-C decreases nearly 30 mV at 10 mA cm−2, while the Tafel slope also reduces 16 mV dec−1 versus CoPt-9/C catalyst. Moreover, a rechargeable Zn-air battery with these composites as air-cathode is self-assembled, and diatomite boosts the battery performance with desirable properties. CoPt-9/Diatomite-C displays the optimal performance, with a power density of 140 mW cm−2, a specific capacity of 616 mA h g−1 at 10 mA cm−2 and an exceedingly robust cycling life. This work provides a viable and cost-effective strategy for fabricating oxygen reversible electrocatalysts for metal-air battery applications.